Penghematan Konsumsi Energi Listrik Rumah Tangga Dengan Penerapan Peak Clipping Dan Strategic Conservation Di Kota Pekanbaru - Reza Muthia; Nurhalim Nurhalim; Dian Yayan Sukma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Household electricity customer is a sector that contribute significantly to affect the high peak loads. This is because in this period people began to turn on the lights, television and other electrical equipment to run its activities which affects the availability of electrical energy. One effort that can be done on the condition that the limited electricity supply that is by saving electrical energy usage by implementing peak clipping and strategicconservation of reducing electricity consumption at times of peak load use power tools are more energy efficient. This research explores the benefits of the implementations of peak clipping and strategic conservation to changes in load pattern and the potency in energy savings. The analysis was focused on the household load of television in Pekanbaru. Based on the calculation and analysis, with application of peak clipping and strategic conservation on the television can increase daily load factor to 12,87%. The potency of energy savings is estimated at 43,99% per day of work.Keywords : load pattern, energy savings, peak clipping, strategic conservation